Performance Evaluation of Server-side JavaScript for Healthcare Hub Server in Remote Healthcare Monitoring System - Nkenyereye, Lionel; Jang, Jong-Wook (Procedia computer science, 2016)
With the help of a small wearable device, patients reside in an isolated village need constant monitoring which may increase access to care and decrease healthcare delivery cost. As the number of patients’ requests increases in simultaneously manner, the healthcare hub server located in the village hall encounters limitations for performing them successfully and concurrently. In this paper, we propose the design tasks of the Remote Healthcare Monitoring application for handling concurrency tasks. In the procedure of designing tasks, concurrency is best understood by employing multiple levels of abstraction. The way that is eminently to accomplish concurrency is to build an object-oriented environment with support for messages passing between concurrent objects. Node.js, a cross-platform runtime environment features technologies for handling concurrency issue efficiently for Remote Healthcare Monitoring System. The experiments results show that server-side JavaScript with Node.js and MongoDB as database is 40% faster than Apache Sling. With Node.js developers can build a high-performance, asynchronous, event-driven healthcare hub server to handle an increasing number of concurrent connections for Remote Healthcare Monitoring System in an isolated village with no access to local medical care.